Energetic Characteristics of Syngas Obtained from Gasification of Hazelnut Prunings. (10th June 2016) - Proto, Andrea R.; Longo, Leonardo; Gambella, Filippo; Zimbalatti, Giuseppe; Macrì, Giorgio; Gallucci, Francesco; Caruso, Luciano; Salerno, Mariangela; Colantoni, Andrea
Abstract: The aim of the study concerns the energy recovery of chips, derived from hazelnut prunings, by means of gasification through air. The gasifier is a downdraft fixed bed reactor, the biomass used is characterized by a moisture of about 16% and a LHV of 15 MJ/kg. The composition of syngas is characterized by a high amount of nitrogen, more than 50% in volume, that is due to use of air as oxidant agent. Results of syngas analysis show that the increase of air flow causes a decrease in hydrogen content but a more marked increase in carbon monoxide and methane contents. The LHV of syngas obtained ranges from 3.2 to 3.6 MJ/Nm 3 and it is suitable to obtain thermal energy that can be used to provide heat for small farms, especially for greenhouses. The gasification system presented is also able to obtain as output flow, in addition to syngas, a solid residue or biochar which can be used in agronomic sector to improve soil characteristics.